Hubungan Kebersihan Genetalia Dengan Diaper Rush Pada Balita Usia 12 Bulan – 36 Bulan Bps Suswati, Sst, M.Mkes Pamekasan - Rohemah; Nova Purmahardini (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Cleanliness is needed for individual comfort, safety, and health. Cleanliness aims to improve skin hygiene, where the skin is the first body line of defense against infection. One of the skin diseases that are often encountered, for example diaper rush. Based on a preliminary study obtained at BPS Suswati, SSTS, M.Mes, the number of children under five in January of 20 children affected by diaper rush was 4 (20%). And the number of toddlers in February was 26 toddlers affected by diaper rush of 7 (35%). This study aims to identify the presence of a factor in genetal hygiene of diaper rush in infants aged 12-36 months at BPS Suswati, SSTS, M.Mes, Pamekasan. This type of research is an analytical survey using a retrospective research design. The population is all infants aged 12 months-36 months with a sample of part of the population of 33 toddlers. Sampling with the technique of probality sampling type Random Sampling data collection using questionnaires. Using Chi-Square analysis. Based on statistical tests using the Chi-Square test with SPSS version 16.0, the Chi-Square value = 0,000 was obtained because the sig value of 0,000